NILAI PENDIDIKAN KARAKTER DALAM SUMANG KECAMATAN TIMANG GAJAH KABUPATEN BENER MERIAH - Siti Nurlaila Sahri; Trisfayani; Safriandi (Global Action and Education for Society, 2026)
This study aims to describe the value of character education in Sumang, Timang Gajah District, Bener Meriah Regency. This type of research is qualitative. The location of this research was carried out in Timang Gajah District, Bener Meriah Regency from May to June 2025. The research data is Sumang customs. The data sources of this research are traditional leaders, religious leaders, and community leaders in Timang Gajah District, Bener Meriah Regency. Data collection techniques in this study are interviews, recordings, and notes. Data analysis techniques in this study are data reduction, data presentation, and conclusions. Based on the results of the study, 36 data were found which are divided into 6 types of character education values, namely religious, honest, tolerant, friendly/communicative, peace-loving, and responsible.